Transient thermal performance of constant fill ratio vapor chamber with different coolants - Songkran WIRIYASART; Paisarn NAPHON (Journal of Thermal Science and Technology, 2021)
In this study, a constant fill ratio vapor chamber using water and ferrofluid as the coolants on the thermal performance and thermal optimization to provide the cooling range are presented. The liquid flow rate of the condenser side ranges from 0.029−0.099 kg/s, the input power of 100−300 W, heat source size of 30 mm × 30 mm, and the water and ferrofluid with φ=0 %, φ=0.005 % and φ=0.05 % as coolants are investigated. The results indicate that the minimum thermal resistance of a traditional vapor chamber of 0.126 ℃/W at m° = 0.075 kg/s and vapor chamber with a mini channel of 0.077 ℃/W at m° = 0.049 kg/s at φ=0.005 % are obtained. The vapor chamber with and without mini channel at a certain fill ratio of 26 % and 33 %, the heat source size of 30 mm × 30 mm, and the mass flow rate of ≥ 0.042 kg/s are withstanding the heat load range from 100–200 W. However, to achieve the high heat load range from 100–300 W, the vapor chamber with mini channel using the Fe3O4 ferrofluid φ=0.005 % is covering the entire cooling range and is recommended in electronic cooling applications.